The War Machine of Fiction: Performing Resistance through Participatory Narrative - Mohajerani, Paria (My University, 2025)
This thesis investigates fictioning as a method of artistic research for reconfiguring political subjectivity and reclaiming agency under conditions of control. Grounded in my personal experience during the Woman, Life, Freedom movement in Iran, the research explores how participatory performance can serve as a site for speculation, resistance, and collective becoming. My artistic project, Blurring the Boundaries: Stories on a Revolution, forms the core of this inquiry. Developed as an immersive, game-like installation, the work invites participants to navigate a branching narrative structure based on real and reimagined moments of protest, surveillance, and escape. Through a series of decision points and sensory stations—including text, sound, and video—participants are asked not to witness, but to choose, reflect, and co-create. Drawing on feminist theory, autotheory, and Deleuze and Guattari’s concept of the war machine, the thesis proposes fictioning not as escapism but as a practice of engaging with the gaps and silences of dominant historical narratives. The work challenges the binary between truth and invention, between activist and non-activist, and resists both the aestheticization and instrumentalization of trauma. By staging a layered, participatory experience that oscillates between memory and speculation, Blurring the Boundaries asks how art can function as a critical and ethical space for rehearsing alternative ways of being—without offering fixed answers or resolutions. It is not a retelling of the past, but an invitation to imagine what else might have been, and what still might come.
Keywords: reshaping narratives of the past; alternative world building; fiction; participants; performance art; LAPS